Temporal transcriptomic profiling identifies core regulators in cytokine-induced gut barrier disruption in differentiated Caco-2 cells - Hyo Shin Yoon; Shining Ma; Matt Kanke; Wan-Jung Wu; Uyen Hoang; Jessica A. Tan; Alex Wilks; Priyanka Patel; Sundeep Chandra; Xin Luo; Daniel Lu; Scott Martin; et al. (Inflammation Research, 2026)
Objective The intestinal epithelial barrier maintains gut homeostasis, and its disruption contributes to inflammatory diseases such as Inflammatory Bowel Diseases (IBD). Although barrier restoration is a promising therapeutic strategy, most current approaches target immune responses rather than epithelial function. Since barrier injury and repair progress through discrete phases, this study aimed to define time-resolved epithelial transcriptional programs and identify candidate regulatory nodes for barrier-focused therapeutic intervention. Methods Differentiated Caco-2 epithelial monolayers were used to model cytokine-induced barrier disruption and profiled by time-resolved bulk RNA-seq. Transcriptional dynamics and candidate regulators were identified using pairwise differential expression, likelihood-ratio testing, pathway enrichment, and upstream-regulator inference. Candidate nodes were tested by pharmacologic perturbation, and disease relevance was assessed by qPCR and histology in human IBD colon tissues. Results Time-resolved profiling revealed dynamic epithelial programs involving the Rho GTPase cycle, sirtuin signaling, non-canonical WNT signaling, and junction/EMT-associated pathways. Upstream-regulator inference highlighted JAK2, TNF, gasdermin D, and β-estradiol, and pharmacologic perturbation of these nodes mitigated cytokine-induced barrier loss. HNF4A emerged as a gut epithelial transcriptional hub regulating targets including SATB2 and SLC26A3. Notably, SLC26A3 was markedly reduced in IBD colon tissues. Conclusions This study provides a time-resolved epithelial framework and highlights therapeutic opportunities for barrier-focused interventions.

Candidate master microRNA regulator of arsenic-induced pancreatic beta cell impairment revealed by multi-omics analysis - Jenna E. Todero; Kieran Koch-Laskowski; Qing Shi; Matt Kanke; Yu-Han Hung; Rowan Beck; Miroslav Styblo; Praveen Sethupathy (Archives of Toxicology, 2022)
Arsenic is a pervasive environmental toxin that is listed as the top priority for investigation by the Agency for Toxic Substance and Disease Registry. While chronic exposure to arsenic is associated with type 2 diabetes (T2D), the underlying mechanisms are largely unknown. We have recently demonstrated that arsenic treatment of INS-1 832/13 pancreatic beta cells impairs glucose-stimulated insulin secretion (GSIS), a T2D hallmark. We have also shown that arsenic alters the microRNA profile of beta cells. MicroRNAs have a well-established post-transcriptional regulatory role in both normal beta cell function and T2D pathogenesis. We hypothesized that there are microRNA master regulators that shape beta cell gene expression in pathways pertinent to GSIS after exposure to arsenicals. To test this hypothesis, we first treated INS-1 832/13 beta cells with either inorganic arsenic (iAs III ) or monomethylarsenite (MAs III ) and confirmed GSIS impairment. We then performed multi-omic analysis using chromatin run-on sequencing, RNA-sequencing, and small RNA-sequencing to define profiles of transcription, gene expression, and microRNAs, respectively. Integrating across these data sets, we first showed that genes downregulated by iAs III treatment are enriched in insulin secretion and T2D pathways, whereas genes downregulated by MAs III treatment are enriched in cell cycle and critical beta cell maintenance factors. We also defined the genes that are subject primarily to post-transcriptional control in response to arsenicals and demonstrated that miR-29a is the top candidate master regulator of these genes. Our results highlight the importance of microRNAs in arsenical-induced beta cell dysfunction and reveal both shared and unique mechanisms between iAs III and MAs III .

Arsenic is more potent than cadmium or manganese in disrupting the INS-1 beta cell microRNA landscape - Rowan Beck; Mohit Chandi; Matt Kanke; Miroslav Stýblo; Praveen Sethupathy (Archives of Toxicology, 2019)